ESSENTIAL FORMULAS INTEGRALS AND TRANSFORMS FOR PHYSICISTS - Y N TIWARI (LONDON NEW CENTRAL BOOK AGENCY, 2013)
This book deals with theoretical as well as experimental problems particularly in atomic and molecular physics, quantum mechanics, nuclear physics and collision theory.
Keywords: MATHEMATICAL PHYSICS; PHYSICS - FORMULAE